2015
DOI: 10.1002/ajim.22413
|View full text |Cite
|
Sign up to set email alerts
|

Serum autoantibodies in silicosis and non‐silicosis cement workers

Abstract: Serum IgA, ASMA, and anti-GBM are the principal immunologic parameters associated with silicosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Silicosis is characterized in part by elevations in serum and bronchoalveolar lavage immunoglobulins in silicosis patients [46,47] and experimentally exposed animals [20]. Another well-known health outcome associated with silica exposure is an increase in the incidence of autoimmune disorders [48,49] including rheumatoid arthritis [50], scleroderma [51], systemic lupus erythematosus [52], and antineutrophilic cytoplasmic antibody-related nephritis [53].…”
Section: Discussionmentioning
confidence: 99%
“…Silicosis is characterized in part by elevations in serum and bronchoalveolar lavage immunoglobulins in silicosis patients [46,47] and experimentally exposed animals [20]. Another well-known health outcome associated with silica exposure is an increase in the incidence of autoimmune disorders [48,49] including rheumatoid arthritis [50], scleroderma [51], systemic lupus erythematosus [52], and antineutrophilic cytoplasmic antibody-related nephritis [53].…”
Section: Discussionmentioning
confidence: 99%
“…Our data showed that serum IgA concentration increased and IgM also elevated. Increasing of IgM was commonly reported in silicosis or silica dust contacted [ 24 26 ], so we speculated the discrepancy may be due to differences between coal mines and, thus, the coal dust composition or different genetic background [ 27 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Beshir et al revealed serum IgA mean level was significantly higher in the silicosis group compared to the non-silicosis group (315.1 AE 165.3 vs. 154.7 AE 105.1 mg/dl, respectively). 13 More interestingly, a recent study may explain the putative link between silicosis and IgA N, which is a NOD-like receptor, pyrin domain-containing 3 (NLRP3). In fact, NLRP3 are the key in the inflammatory process caused by silica: they are involved, in association with alveolar macrophages, in binding and eliminating crystalline silica particles, and thus leading to pulmonary fibrosis in recent studies.…”
Section: Discussionmentioning
confidence: 99%